2012
DOI: 10.1002/bin.1336
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Preference for Social Interaction in Children Diagnosed With Autism

Abstract: In this study, preference for social interaction was investigated for three young children diagnosed with autism. The study consisted of conducting a multiple stimulus without replacement preference assessment to determine a hierarchy of preference for the interactions and conducting a reinforcer assessment. Results showed several types of social interaction functioned as reinforcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 12 publications
2
29
0
Order By: Relevance
“…The current study extended previous research on picture‐based MSWOs for assessing preference for social interaction (Lang et al, ; Nuernberger et al, ) by delineating which skills correlate with valid MSWO hierarchies. In the current study, for participants who communicated vocally and identified pictures of social interactions (i.e., Edgar and Ned), the aggregated MSWO produced accurate hierarchies, despite including fewer sessions and less exposure to the contingencies.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The current study extended previous research on picture‐based MSWOs for assessing preference for social interaction (Lang et al, ; Nuernberger et al, ) by delineating which skills correlate with valid MSWO hierarchies. In the current study, for participants who communicated vocally and identified pictures of social interactions (i.e., Edgar and Ned), the aggregated MSWO produced accurate hierarchies, despite including fewer sessions and less exposure to the contingencies.…”
Section: Discussionsupporting
confidence: 70%
“…Recently, researchers have evaluated several different methods for assessing preference for social interactions (Clay et al, ; Huntington & Higbee, ; Kelly et al, ; Lang et al, ; Morris & Vollmer, , ; Nuernberger et al, ; Wolfe et al, ). Each of these studies described a method of preference assessment that was effective at identifying preferred and reinforcing social interactions.…”
Section: Studies Evaluating Methods Of Assessing Preference For Sociamentioning
confidence: 99%
“…The studies reviewed suggest that preference toward social stimuli was frequently assessed with pictures (drawings, photos), which are only amenable to MSWO and PWPA methods. For instance, Nuernberger, Smith, Czapar, and Klatt (2012) assessed an array of social stimuli using MSWO and found that preference predicted the reinforcing value of social activities in two of the three participants in the study; i.e., participants complied with task instructions to gain access to the social stimuli. However, the assessment of preference using pictorial stimuli may be amenable only to individuals with picture-tangible matching skills (Conyers et al, 2002;Clevenger & Graff, 2005).…”
Section: Descriptive and Qualitative Analyses Of The Literaturementioning
confidence: 99%
“…Clay et al, 2013). Lang et al (2014) used pretraining sessions that lasted 20 and 40 min while the other researchers (Kelly et al, 2014;Nuernberger et al, 2012) conducted exposures to the contingencies prior to the beginning of the assessment to aid the development of stimulus control.…”
Section: University Of Floridamentioning
confidence: 99%